Surgical Treatment of Congenital Hallux Varus - Shim, Jong Sup (The Korean Orthopaedic Association, 2014)
BACKGROUND: The purpose of this study was to report outcomes of congenital hallux varus deformity after surgical treatment. METHODS: We evaluated ten feet of eight patients with a congenital hallux varus deformity, including four feet combined with a longitudinal epiphyseal bracket (LEB). There were seven male patients and one female patient with a mean age of 33 months (range, 7 to 103 months) at the time of surgery. Two patients were bilaterally involved. The mean duration of follow-up was 5.9 years (range, 2.3 to 13.8 years). Clinical outcomes were assessed according to the criteria of Phelps and Grogan. Surgical procedures included the Farmer procedure, the McElvenny procedure or an osteotomy at the first metatarsal or proximal phalanx. RESULTS: The clinical results were excellent in two feet, good in six and poor in two feet. The LEB was associated with hallux varus in four feet and were treated by osteotomy alone or in conjunction with soft tissue procedure. CONCLUSIONS: Congenital hallux varus was successfully corrected by surgery with overall favorable outcome. Preoperatively, a LEB should be considered as a possible cause of the deformity in order to prevent recurrent or residual varus after surgery.